Christopher Columbus - Scavone, Daniel C., 1934- (San Diego, CA : Lucent Books, 1992)
A biography of explorer Christopher Columbus, from his early life, to his three voyages, to his mixed legacy.
Includes bibliographical references (p. 90-92) and index.
Keywords: Columbus, Christopher -- Juvenile literature; Columbus, Christopher; Explorers -- Biography -- America; Explorers -- Biography -- Spain; Explorers; America -- Discovery and exploration